2011
DOI: 10.1161/strokeaha.110.596361
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Stroke in Patients With Bullous Pemphigoid

Abstract: Background and Purpose-Although previous research reveals that cardiovascular events and thromboembolic diseases are important causes of death in patients with bullous pemphigoid (BP), the risk of stroke after the diagnosis of BP relative to the general population remains unknown. Using a randomly selected nationwide population-based sample, this study investigates the risk of stroke in patients with BP compared with unaffected individuals of a similar age. Methods-This study analyzes data from Taiwan's Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
66
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 49 publications
6
66
2
Order By: Relevance
“…The previous studies, except the ones considering motor neuron diseases 8 and strokes 15 , have most probably missed this connection because of small study populations or short follow-up time. Still, the 2-fold increased risk of viral meningitis or viral encephalitis following a diagnosis of BP was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies, except the ones considering motor neuron diseases 8 and strokes 15 , have most probably missed this connection because of small study populations or short follow-up time. Still, the 2-fold increased risk of viral meningitis or viral encephalitis following a diagnosis of BP was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, one study suggested that cardiovascular events and thromboembolic diseases are important causes of death in patients with BP; the risk of stroke after a diagnosis of BP (relative to the general population) was investigated in Taiwan. The study sample included 390 patients with BP, versus 1950 matched subjects in a comparison group [14]. Other authors have also reported statistically significant cardiovascular and neurologic alterations between patients affected by BP and matched control groups [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…The study sample included 390 patients with BP, versus 1950 matched subjects in a comparison group [14]. Other authors have also reported statistically significant cardiovascular and neurologic alterations between patients affected by BP and matched control groups [14][15][16][17][18]. As we have previously noted, most classic skin immunofluorescence studies have been performed with monofluorochome techniques, frequently utilizing FITC.…”
Section: Discussionmentioning
confidence: 99%
“…The association between these dermatoses and AIS may be causal and possibly explained by intrinsic inflammatory physiopathological abnormalities leading to thrombosis and hypercoagulability [3,4,5,6,7]. However, whether the overrepresentation of traditional risk factors may be a potential contributor for the higher incidence of AIS observed in some cohorts of patients with dermatoses is currently unknown [7,8,9,10,11,12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…There is limited data on the epidemiology and prevalence of risk factors within these dermatoses in AIS populations, aside from the information derived from studies based on outpatient populations [3,7,8,15,16]. To this end, the primary objective of this study was to assess the prevalence of systemic diseases associated with dermatoses in admissions of AIS patients in the USA, with specific examination of traditional risk factors.…”
Section: Introductionmentioning
confidence: 99%